A Simulation Study of Effect of Mn-Ce/γ-Al2O3 on NOx Storage and Reduction over Pt-Ce-Ba/γ-Al2O3 Catalysts - Lili Lei; Chuan Sun; Bo Zhang; Wenye Gu (Advances in Materials Science and Engineering)
A series of Pt-Ce-Ba/γ-Al2O3 and Mn-Ce/γ-Al2O3 catalysts were synthesized by a sol-gel method and the samples were characterized by XRD, SEM, and EDS. The effect of Mn-Ce/γ-Al2O3 on the storage and reduction of NOx over Pt-Ce-Ba/γ-Al2O3 catalysts was studied in a fix-bed reactor with simulation gases NO, O2, and N2. The results indicated that NO oxidation to NO2 was reduced with the increase of inlet NO concentration, which was up to 83% when the concentration of NO was 500 ppm but reduced to 76% with the concentration of NO increasing to 1000 ppm. Comparing with the Pt-Ce-Ba/γ-Al2O3 catalysts, the rate of NOx storage and reduction was remarkably increased over Pt-Ce-Ba/γ-Al2O3 combined with Mn-Ce/γ-Al2O3 catalysts. However, the reductant used for NOx reduction reaction over Pt-Ce-Ba/γ-Al2O3 catalysts was consumed under the treatment of Mn-Ce/γ-Al2O3 catalyst, which caused the NOx conversion to obviously drop, but the rate of NOx absorption declined slightly.